A Drop of the Irish: The Influence of Irish Folksong on Newfoundland’s Song Tradition - Neilands, Colin (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1992)
This article examines the possible influences of Ireland, through the waves of eighteenth and nineteenth century immigrants, in current Newfoundland folksong repertoire. While much of the findings must remain speculative, given ail the limitations surrounding sources on both sides of the Atlantic, the research revealed that 143 songs collected in field-recordings in Newfoundland this century could have originated in, or have passed through and been influenced by, the Irish folksong tradition. Newfoundland has developed its own strong native song tradition, but in repertoire and style the Irish roots of many of its people still have Iife and vibrancy.